Pressure Swing Adsorption Technologies for Carbon Dioxide Capture. Issue 2 (2nd April 2016) - Wiheeb, A. D.; Helwani, Z.; Kim, J.; Othman, M. R.
Abstract : The principles of pressure swing adsorption (PSA) for carbon dioxide capture are reviewed. Previous work on PSA, relevant modeling and experimental investigation for specifically carbon dioxide separation are also presented and significant findings highlighted. Simple rules for PSA process design based on analysis of the inherent properties of adsorbate-adsorbent systems encompassing equilibrium isotherm, adsorption kinetics, shape of breakthrough curves, screening and selection of adsorbent, bed porosity, adsorption time, purge to feed ratio, residence time, pressure equalization and rinse steps are provided to promote better understanding of the technology so that it gains wider acceptance in the future to address the global environmental concern, particularly in the removal of carbon dioxide as a greenhouse gas.